Creative city: A new challenge of strategic urban planning? - Christina Vlachopoulou; Alex Deffner (European Regional Science Association (ERSA), 2011)
`Sustainable' city, `entrepreneurial' city, `smart' city, `normal' city are some of the most popular characterisations given to cities by urban planners in their attempt to configure the necessary development features of contemporary urban space. The aim of these characteristics is the combination of the factors that a `successful' city should have: good conditions for residents providing them with job opportunities and leisure activities, promotion of culture, and response to current challenges of the global competitive market in the context of sustainability and environmental protection. Creative city seems to accomplish these prerequisites. Creative city refers to a new theory (method?) of strategic planning for urban space and examines the way people act, plan and think creatively. It also highlights the importance of human potential, since at the heart of the creative city are `creative people' encouraged to connect their vision with local urban policies. The aim of the paper is to investigate the way and the extent that the creative city could be considered as a contemporary instrument of strategic urban planning. The analysis will include the examination of the criteria that determine creativity, as well as the way that these criteria are engaged in the development process. Key-words: creative city, creativity, strategic urban planning, leisure
Keywords: 330